Economic Profit Determinants of Large-scale Russian Companies - ИвашковскаяИрина Васильевна; КукинаЕлизавета Борисовна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
Residual income provides the foundation for the new system of measurers based on the criterion of value creation and it is used for strategic performance evaluation on yearly basis. We use the panel data for the sample of 26 large-scale Russian firms with the financial reports in IAS for the period of 2002-2007 to identify key determinants of economic profit. We found that capital expenditures, the growth of revenue, operating margin and dividends are among statistically significant independent variables. On the contrary, capital structure, short term versus long term debt financing, government ownership and pay benefits to top management can’t be considered determinants of residual income for the sample. E-mail: ivashkovskaya@yandex.ru